Bone regeneration after demineralized bone matrix and castor oil (Ricinus communis) polyurethane implantation - Leite,Fábio Renato Manzolli (2008)
Innocuous biocompatible materials have been searched to repair or reconstruct bone defects. Their goal is to restore the function of live or dead tissues. This study compared connective tissue and bone reaction when exposed to demineralized bovine bone matrix and a polyurethane resin derived from castor bean (Ricinus communis). Forty-five rats were assigned to 3 groups of 15 animals (control, bovine bone and polyurethane). A cylindrical defect was created on mandible base and filled with bovine bone matrix and the polyurethane. Control group received no treatment. Analyses were performed after 15, 45 and 60 days (5 animals each). Histological analysis revealed connective tissue tolerance to bovine bone with local inflammatory response similar to that of the control group. After 15 days, all groups demonstrated similar outcomes, with mild inflammatory reaction, probably due to the surgical procedure rather than to the material. In the polymer group, after 60 days, scarce multinucleated cells could still be observed. In general, all groups showed good stability and osteogenic connective tissue with blood vessels into the surgical area. The results suggest biocompatibility of both materials, seen by their integration into rat mandible. Moreover, the polyurethane seems to be an alternative in bone reconstruction and it is an inexhaustible source of biomaterial.